THE CONSTRUCTION OF CHILDREN MORAL REASONING IN STRENGTHENING SELF-CONTROL - U'um Qomariyah; Qurrota Ayu Neina (Universitas Negeri Makassar, 2020)
Self-control is achieved by popular children stories, by which they are able to help children see themselves and change their way of life to ensure a sustainable future. Besides, the stories also function to identify, investigate, evaluate, and take appropriate actions in order to maintain, protect, and develop one’s mentality and characters, environment, and society. The purpose of this study was to reveal the construction of children moral reasoning in children stories contained in a national daily newspaper of Suara Merdeka in 2018. As based on the research substance, this present study relied on the qualitative and critical analysis methods. The results suggests that children, as the main characters in every story, have morals and do reasoning in dealing with problems. The construction of moral reasoning is classified into three, i.e., construction of moral reasoning in children’s relationship with family, with friends, and with society. Such constructions will give relevance to children's self-control in solving various problems and coping with pressures.